2003
DOI: 10.1353/jaas.2004.0004
|View full text |Cite
|
Sign up to set email alerts
|

Being American Between Black and White: Second-Generation Asian American Professionals' Racial Identities

Abstract: This article examines the racial identities of second generation Korean and Indian Americans living in Dallas, Texas, relative to both Whites and Blacks, in order to elucidate their racialization. Korean and Indian Americans criticized White racism yet asserted that they were equal "Americans" to Whites, who did not deserve to be targeted. They accomplished this by differentiating themselves from Blacks whom they regarded, ironically, as the true foreigners. Why only a quarter of interviewees felt tied to Blac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
36
0

Year Published

2008
2008
2019
2019

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 38 publications
(37 citation statements)
references
References 35 publications
1
36
0
Order By: Relevance
“…1), idealized patriarchal beliefs about gender will positively relate to group pride which will positively relate to resilience, which in turn will negatively relate to depression. In the context of Asian American stereotypes as the "model minority" because of their perceived economic and educational success, this study examined Asian Americans' reported pride as members of this successful immigrant group (Dhingra 2003;Espiritu 2001).…”
Section: Immigration and Idealized Beliefs About Gendermentioning
confidence: 99%
See 1 more Smart Citation
“…1), idealized patriarchal beliefs about gender will positively relate to group pride which will positively relate to resilience, which in turn will negatively relate to depression. In the context of Asian American stereotypes as the "model minority" because of their perceived economic and educational success, this study examined Asian Americans' reported pride as members of this successful immigrant group (Dhingra 2003;Espiritu 2001).…”
Section: Immigration and Idealized Beliefs About Gendermentioning
confidence: 99%
“…Although the validity of the model minority myth has been questioned due to the varying success among Asian Americans (Cheng 1997;Lee 1994;Woo 2000), Asian Americans do endorse the image of Asian Americans as exemplars of American ideals, such as "pulling yourself up by your bootstraps" against all odds through sheer hard work and perseverance (Chun and Sue 1998;Dhingra 2003;Hune and Chan 1997). Gender also anchors these idealized positive constructions of group identity, which reinforces the appropriateness of the ICI model in Asian American communities (Mahalingam 2006).…”
Section: Immigration and Idealized Beliefs About Gendermentioning
confidence: 99%
“…The different attitudes toward race between first and second generation Indians in the United States has certainly been noted by other scholars (Visweswaran 1997;Khandelwal 2002;Koshy 2002;Dhingra 2003;Kurien 2005;Bhatia 2007). For a broader discussion of the concept of brownness among Latinos and Asian Americans, see Eileen O'Brien's (2005) provocative analysis of the "racial middle."…”
Section: Resultsmentioning
confidence: 68%
“…Asian-Americans experience discrimination in many different ways, including hate crimes, racial profiling, and barriers to college admission (Dhingra, 2003). The most well-known form of discrimination is stereotyping.…”
Section: Model Minority Statusmentioning
confidence: 99%
“…AsianAmericans use financial and academic success to gain social desirability where they are inherently unable to achieve it, being non-white. The social ceiling, or the symbolic barrier to minority groups achieving social parity with whites, is present because of physical differences that are present between Asian-Americans and whites (Dhingra, 2003). In Dhingra's 2003 collection of interviews, Tammy, an Asian-American actress, speaks about this.…”
Section: Model Minority Statusmentioning
confidence: 99%